Impact of body mass index on surgical and oncological outcomes after Hyperthermic Intraperitoneal Chemotherapy (HIPEC). - Anne-Cécile Ezanno; Olivier Poudevigne; Jean-Louis Quesada; Julio Abba; Brice Malgras; Bertrand Trilling; Pierre-Yves Sage; Juliette Fischer; Marc Pocard; Catherine Arvieux; Fatah Tidadini (PLoS ONE, 2025)
Background Complete cytoreductive surgery with Hyperthermic intraperitoneal chemotherapy (HIPEC) is the standard treatment for patients with peritoneal metastases. In this retrospective observational two-center study, we assessed the impact of patient's body mass index (BMI) on surgical and oncological outcomes. Methods Between 2017 and 2021, 144 patients with peritoneal metastases (all etiologies) were included. Morbi-mortality at day-30, overall survival and free-recurrence-survival were compared according to the patients BMI. The patients were divided into 2 groups (BMI < 25, and BMI ≥ 25). Results Median overall survival (OS) was 71.3 months [63-71.5], with significant differences observed between BMI groups (p = 0.015). Recurrence-free survival (RFS) averaged 26.8 months [20-35.3] and did not significantly differ between groups (p = 0.267). After stratification by histology, OS and RFS remained consistent. Cox multivariate analysis adjusted for Peritoneal Carcinomatosis Index (PCI) revealed BMI < 25 (HR = 2.53 [1.10-5.80]) and male sex (HR = 2.34 [1.11-4.92]) as predictors of poorer OS. 30-Day complication rates did not significantly differ (p = 0.094). The BMI ≥ 25 group experienced higher rates of digestive fistulas (p = 0.05) and 90-day readmissions (p = 0.007), although reintervention rates were comparable (p = 0.723). Conclusions Our study suggests a potential 'obesity paradox' in the context of HIPEC procedures. Morbidity at day-30 was similar for BMI < 25, and BMI ≥ 25 patients. Readmissions at day-90 were more frequent in high-BMI group. BMI < 25 is deleteriously associated with mortality. BMI and sex were related to OS.